Psychological Foundations of Mind Mapping Strategies - Buchatska, Svitlana (East European Journal of Psycholinguistics, 2016)
The present study investigates psychological foundations of mind mapping as one of the relevant tools in teaching and learning process. A Mind Map, the modern approach implemented and developed by Tony Buzan is viewed as a visual diagram used to record and organise information in a way which the brain finds captivating and easy to process. It is based on the conception of radial tree, diagramming key words in a colorful, radiant, tree-like structure. The study focuses on the theoretical analysis of brain’s as well as cerebral hemispheres’ functioning aiming to explain the claimed increased effectiveness of mind mapping over other forms of learning, understanding, remembering and performing. Much attention is devoted to the benefits and challenges of using mind maps. Thus, some sufficient mind mapping strategies for English teachers which can be effectively used in the classroom have been presented. The research confirms that mind mapping is a beneficial learning tool to help students brainstorm any topic and think creatively. It is a powerful way for students to reach high levels of cognitive performance. References Abi-El-Mona, I., & Ad-El-Khalick, F (2008). The Influence of Mind Mapping on Eighth Graders’ Science Achievement. School Science and Mathematics, 108, 298-312. Buchatska, S. (2015). Anxiety factors of students’ emotional disposition to professional communication in foreign languages. East European Journal of Psycholinguistics. 2(1), 3–10. Buzan, T. and Buzan, B. (1993). The mind map book: How to use radiant thinking to maximize your brains untapped potential. Dutton. Buzan, T., & Buzan, B. (2010). The Mind Map Book. Unlock your creativity, boost your memory, change your life. Harlow, England: Pearson. Cunningham, W. A., Raye, C. L., & Johnson, M. K. (2005). Neural correlates of evaluation associated with promotion and prevention regulatory focus. Cognitive, Affective, & Behavioral Neuroscience, 5, 202-211. Farrand, P., Hussain, F., & Hennessey, E. (2002). The efficacy of the ‘mind map’ study technique. Medical Education, 36, 426-431. Gardner, H. (1993). Multiple Intelligences. New York: Basic Books. Novak, J. D., & Cañas, A.J. (2008). The Theory Underlying Concept Maps and How to Construct and Use Them. Institute for Human and Machine Cognition. Pensacola Fl. Retrieved from http://www.ihmc.us. Paivio, A. (1971). Imagery and Verbal Processes. New York: Holt, Rinehart and Winston. (Republished in 1979 – Hillsdale, NJ: Erlbaum.) Yates, F.A. (1966). The Art of Memory. London: Routledge and Kegan Paul.